The challenges of impact evaluation: Attempting to measure the effectiveness of community-based disaster risk management. (October 2020) - Sarabia, Maria M.; Kägi, Alfredo; Davison, Anthony C.; Banwell, Nicola; Montes, Carlos; Aebischer, Christina; Hostettler, Silvia
Abstract: Although disaster risk management is becoming increasingly important in development cooperation, there is still a lack of robust evidence regarding its effectiveness. Few studies based on a counterfactual have been conducted in the fields of disaster management and disaster risk reduction. This article describes a methodological approach to enabling more rigorous evidence-based decision-making in community-based disaster risk mitigation, and notably for assessing the degree to which it increases preparedness for the adverse effects of hazards in vulnerable communities. The effects of actions designed to reduce disaster-induced loss, damage, injuries, fatalities and resource degradation were evaluated at a Swiss and Honduran Red Cross' intervention area in Honduras. Our results show that the intervention has had a significant positive effect in three important areas of resilience: knowledge and preparedness (e.g., existence of an early warning system); social cohesion (e.g., community institutions); and management of natural assets (e.g., firewood consumption). Our findings indicate that the intervention program has enhanced the capacities of treated communities to prepare for future hazards and to respond in case of an emergency at both household and community levels.